Dream Psychology of North Korean Defectors in South Korea: Implicit Learning and Social Adjustment - Jinhee Choi (Adult Education Research Conference, 2018)
This paper applies the theoretical framework of Fromm’s humanistic psychology to examine the reported content of North Korean defectors’ dreams during sleep and considers what the psychological data suggests about the defectors' past social experience in authoritarian North Korea and their present social situation as adults learning to adjust to a new life in neo-liberal South Korea.
Keywords: adult defectors; Erich Fromm; Korean peninsula; nightmares; sleep experiences; social psychology